"Obesity Is a Disease": Examining the Self-Regulatory Impact of This Public-Health Message. (April 2014) - Hoyt, Crystal L.; Burnette, Jeni L.; Auster-Gussman, Lisa
In the current work, we examined the impact of the American Medical Association's recent classification of obesity as a disease on weight-management processes. Across three experimental studies, we highlighted the potential hidden costs associated with labeling obesity as a disease, showing that this message, presented in an actual New York Times article, undermined beneficial weight-loss self-regulatory processes. A disease-based, relative to an information-based, weight-management message weakened the importance placed on health-focused dieting and reduced concerns about weight among obese individuals—the very people whom such public-health messages are targeting. Further, the decreased concern about weight predicted higher-calorie food choices. In addition, the disease message, relative to a message that obesity is not a disease, lowered body-image dissatisfaction, but this too predicted higher-calorie food choices. Thus, although defining obesity as a disease may be beneficial for body image, results from the current work emphasize the negative implications of this message for self-regulation.